Study of therapeutic effects of nebulized adrenaline alone, nebulized adrenaline plus injectable dexamethasone (in combination) and nebulized 3% hypertonic saline alone in clinically diagnosed cases of bronchiolitis - Verma, Ishwari Prasad; Garg, Pukhraj; Karnawat, B. S.; Jain, Anil; Verma, Pradeep; Kumawat, Rakesh (International Journal of Contemporary Pediatrics, 2017)
Background: Bronchiolitis is a common respiratory tract infection in young children. Respiratory Syncytial Virus (RSV) is the common etiological agent, with highest incidence occurring between December and March. 90% of children are infected in the first 2 years of life. Infants hospitalized are more likely to have respiratory problems as older children, especially recurrent wheezing. The treatment is mainly supportive. Mild cases are managed with antipyretics, hydration and home remedies/cough formulas. Moderate cases may require humidified oxygen, parenteral fluids to maintain hydration and nebulization with bronchodilators. Nebulization with adrenaline along with IV dexamethasone more effective in terms of reduction in the duration of the symptoms and length of hospital stay. Methods: This prospective study was done for 1 year from May 2015 onwards.120 clinically diagnosed cases of bronchiolitis were included. cases were classified into 2 groups on the basis of RDAI score, Mild cases with score of 4-15 &Severe cases with score of >15. All cases were divided in 3 therapeutic groups, A- nebulized with adrenaline alone, B- single dose of IV dexamethasone and nebulized adrenaline, C- nebulized with 3% hypertonic saline alone. Nebulization was done at 0,30,60 minutes interval and then 4 hourly till improvement of symptoms. Results: Out of total 120 cases,74(61.66%) belonged to age group of 2-6 months. Males were more affected than females with ratio of 2.15:1. Most of patients (83.3%) had hyperinflated lung field in X-ray finding. Children with preterm birth had severe disease. The mean RDAI score was found to be reduced highest in adrenaline plus dexamethasone group that is 2.37±0.80 within 24 hours of admission with 26.24% reduction in the length of hospital stay as compared to group A and 20.61% as compared to group C. Conclusions: combination of nebulized adrenaline and dexamethasone is better in terms of reducing clinical severity, length of hospital stay in children with moderate severity of acute bronchiolitis in comparison to adrenaline alone and 3% hypertonic saline alone.